2022
DOI: 10.3390/cells11050897
|View full text |Cite
|
Sign up to set email alerts
|

PTH-Induced Bone Regeneration and Vascular Modulation Are Both Dependent on Endothelial Signaling

Abstract: The use of a bone allograft presents a promising approach for healing nonunion fractures. We have previously reported that parathyroid hormone (PTH) therapy induced allograft integration while modulating angiogenesis at the allograft proximity. Here, we hypothesize that PTH-induced vascular modulation and the osteogenic effect of PTH are both dependent on endothelial PTH receptor-1 (PTHR1) signaling. To evaluate our hypothesis, we used multiple transgenic mouse lines, and their wild-type counterparts as a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…[ 22,23 ] Both PTH‐induced bone regeneration and vascular regulation depend on endothelial signal transduction, and when PTHR1 in endothelial cells is knocked out, the formation of PTH‐induced narrow blood vessels is significantly reduced and the osteogenesis of PTH is weakened. [ 24 ] Only inducing the PTH axis in osteoblasts is not enough to induce bone formation. Therefore, promoting angiogenesis is equally important in the repair of osteoporotic bone defects.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22,23 ] Both PTH‐induced bone regeneration and vascular regulation depend on endothelial signal transduction, and when PTHR1 in endothelial cells is knocked out, the formation of PTH‐induced narrow blood vessels is significantly reduced and the osteogenesis of PTH is weakened. [ 24 ] Only inducing the PTH axis in osteoblasts is not enough to induce bone formation. Therefore, promoting angiogenesis is equally important in the repair of osteoporotic bone defects.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study demonstrated that intermittent PTH administration promoted the proliferation and migration of fibroblasts, which contribute to improved wound healing (Shen et al., 2020). In addition, intermittent PTH administration has shown the ability to induce angiogenesis and vascular modulation of small‐diameter blood vessels through the endothelial cell PTHR (Cohn Yakubovich et al., 2017; Cohn‐Schwartz et al., 2022). Moreover, intermittent PTH administration has been reported to stimulate the proliferation and migration of endothelial cells (Shen et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal investigations have suggested that the increase of PTH triggers the transformation of aortic endothelial cells into chondrocytes 171 and the PTH receptor 1 (PTHR1) signaling of endothelial cells plays a pivotal role in PTH-induced osteogenesis and is correlated to angiogenesis. 192 It is acknowledged that insulin resistance is closely associated with diabetes, and insulin stimulates the release of endothelial NO, which in turn oxidizes lipoproteins, decelerates the rate of intimal calcification, and suppresses vasa vasorum formation. 128 Upon the occurrence of insulin resistance (IR), the higher concentration of free fatty acids in the liver prompts the body to amplify the absorption and very low-density lipoprotein (VLDL) triglyceride production and secretion to compensate; therefore, the susceptibility to blood vessel calcification escalates.…”
Section: Introductionmentioning
confidence: 99%